(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To determine the potential outcome of retrograde intramedullary nailing in supracondylar femur fractures in terms of fracture union and range of knee movement. Methods: This descriptive case series study was conducted from June 2015 to November 2015. Study included 31 patients of either gender aged between 18-60 years presenting with supracondylar femoral fractures type 33A 1,2,3 which were fixed by retrograde interlocking nail technique using C-arm to make entry point and locking of nail. All patients were operated by one team in District Hospital Quarter Hospital Faisalabad. Outcome variable were frequency of union and functional outcome of knee range of motion Results: The mean age of the patients was 38.77±9.70 years with a male to female ratio of 5:1. Radiological and clinical union was established in 30 (96.8%) patients at 24th post-operative week while 1 (3.2%) patient was labeled to have non-union. The range of knee flexion increased gradually from 99.94±9.98 degrees on 10th post-operative day to 122.13±8.64 degrees on 24th post-operative week Conclusion: Retrograde interlocking nail is an effective treatment option for supracondylar femur fractures with excellent union rate and functional range of motion at knee